Fiber Bragg Grating-Based Performance Monitoring of Piles Fiber in a Geotechnical Centrifugal Model Test - Xiaolin Weng; Jianxun Chen; Jun Wang (Advances in Materials Science and Engineering)
In centrifugal tests, conventional sensors can hardly capture the performance of reinforcement in small-scale models. However, recent advances in fiber optic sensing technologies enable the accurate and reliable monitoring of strain and temperature in laboratory geotechnical tests. This paper outlines a centrifugal model test, performed using a 60 g ton geocentrifuge, to investigate the performance of pipe piles used to reinforce the loess foundation below a widened embankment. Prior to the test, quasidistributed fiber Bragg grating (FBG) strain sensors were attached to the surface of the pipe piles to measure the lateral friction resistance in real time. Via the centrifuge actuator, the driving of pipe piles was simulated. During testing, the variations of skin friction distribution along the pipe piles were measured automatically using an optical fiber interrogator. This paper represents the presentation and detailed analysis of monitoring results. Herein, we verify the reliability of the fiber optic sensors in monitoring the model piles without affecting the integrity of the centrifugal model. This paper, furthermore, shows that lateral friction resistance developed in stages with the pipe piles being pressed in and that this sometimes may become negative.